Influences on preschool teachers' willingness to persist in implementing STEM activities: An investigation in Vietnam - Nguyen Manh-Tuan; Nguyen Thi Thanh Tuyen; Nguyen Tien-Trung (Journal of Technology and Science Education)
Pre-school years are considered a natural starting point for STEM education. Along with state policies, school support, and other resources, teachers play a crucial role in the successful implementation of STEM education at kindergartens. The issue of professional development for teachers to implement STEM education in preschools has been discussed in several studies. To identify the factors affecting the intention of preschool teachers to sustain the practice of STEM / STEAM education, the study uses individual behaviour prediction models based on the factors with potential influence on teachers’ decisions. A qualitative study was conducted with a sample of 1278 in-service preschool teachers in Vietnam. The preliminary results of the research show that the most influential factors that affect the intention of Vietnamese preschool teachers to maintain STEM/STEAM education activities are the perceived behavioural control of teachers with STEM/STEAM education, including teacher self-efficacy in STEM/STEAM education, and facilitating conditions for STEM/STEAM education. Hence, the study recommends that stakeholders should enhance professional development for preschool teachers, improve the STEM/STEAM education curriculum, provide favourable infrastructure, and implement supportive policies to boost preschool teachers' confidence and teaching capabilities in STEM/STEAM education.